Turtle geometry in computer graphics and computer-aided design - Goldman, Ron; Schaefer, Scott; Ju, Tao (Computer aided design, 2004)
LOGO is a programming language incorporating turtle graphics, originally devised for teaching computing to young children in elementary and middle schools. Here, we advocate the use of LOGO to help introduce some of the basic concepts of computer graphics and computer-aided design to undergraduate and graduate students in colleges and universities. We shall show how to motivate affine coordinates and affine transformations, fractal curves and iterated function systems, relaxation methods and subdivision schemes from elementary notions in turtle geometry and turtle programming.